A First Millennium A.D. Vegetation History from the Crystal River Site (8CI1), Florida. (2nd January 2020) - Jackson, Kendal; Pluckhahn, Thomas J.
Abstract: While seldom integrated within coastal archaeological research in Southeastern North America, vegetation histories derived from palynological data offer valuable records of ancient landscape transformations driven by climatic flux, sea-level oscillations, and anthropogenic modifications. In this paper, we develop a paleo-historical-ecological reconstruction from preliminary analyses on fossil pollen assemblages preserved within marsh, hammock, and shell-midden soils at the Crystal River site (8CI1), a mound center on Florida's west-central coast occupied throughout the first millennium AD. When contextualized alongside paleoenvironmental records from western Florida and farther afield, our analysis suggests that the nature and timing of late-Holocene climatic changes varied little between different sub-regions of Florida's Gulf Coast, but also that manifestations of eustatic sea-level flux may have been highly localized.